Amlodipine and Xerostomia in elderly patients - Mustafa Al-Ahmad, Basma Ezzat; Mustafa, Nazih Shaban; Kashmola, Muhanad Ali Hamdon; Ismail, Azlini; Mohd, Farah Natashah; Mohd Ibrahim, Mohamad Shafiq; Che Musa, Muhd Firdaus; Abdul Qader, Omar Abdul Jabbar (The Ektodermal Displazi Gurubu Türkiye, 2023)
Hypertension is one of the most common chronic diseases worldwide. The prevalence of hypertension in the elderly is high and many of them are taking different types of antihypertensive medications including Amlodipine. Xerostomia and hyposalivation can have a detrimental effect on a patient’s quality of life leading to situations such as stress or anxiety. In this study, the relationship between Amlodipine as an antihypertensive drug and xerostomia in elderly patients was evaluated. 72 patients of both genders aged 65-75 taking amlodipine for the last 3 years were involved in the study. Those patients have shown xerostomia or hyposalivation in variable degrees. The percentage of xerostomia in the medicated hypertensive group of the present study was higher in males (22 %) than those in females (20 %) which was not significant (p = 0.705). However, a statistically significant difference (p = 0.003) between amlodipine and xerostomia status was observed which was higher in males (34.7 %) than that in females (26.4%). This study assures that elderly patients taking Amlodipine are at high risk of having xerostomia and hyposalivation